2010
DOI: 10.1002/chem.200902099
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Intramolecular Charge Transfer in Oligoyne‐Linked Donor–π–Acceptor Molecules

Abstract: his is the peer reviewed version of the following rtileX ¦ lssonD vFEyFD ngD gFD ftsnovD eFFD uingD FwFD feeyD eFD wonkmnD eFF fryeD wFF @PHIHAF i0ient sntrmoleulr ghrge rnsfer in yligoyneEvinked honor!!eeptor woleulesF ghemistry E e iuropen tournl IT@SAX IRUHEIRUWD whih hs een pulished in (nl form t httpsXGGdoiForgGIHFIHHPGhemFPHHWHPHWWF his rtile my e used for nonEommeril purposes in ordne ith ileyEgr erms nd gonditions for selfErhivingF Additional information: Use policyThe full-text may be used and/or repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…The oxidation potential of 0.46 V for 1, assigned to the one-electron oxidation of the triarylamine unit, decreases to 0.40-0.42 V for the longer molecules 2-5 ( Figure 1). [29,30] The symmetrical D--D compound 6 contains two oxidation waves only 120 mV apart, corresponding to sequential oxidations at the two (electronically interacting) triarylamine units. [31] Additional oxidation waves ascribed to the bridge unit are also observed at higher potentials (0.65-0.88 V) which shift cathodically from 2 to 5.…”
Section: Solution Electrochemistrymentioning
confidence: 99%
“…The oxidation potential of 0.46 V for 1, assigned to the one-electron oxidation of the triarylamine unit, decreases to 0.40-0.42 V for the longer molecules 2-5 ( Figure 1). [29,30] The symmetrical D--D compound 6 contains two oxidation waves only 120 mV apart, corresponding to sequential oxidations at the two (electronically interacting) triarylamine units. [31] Additional oxidation waves ascribed to the bridge unit are also observed at higher potentials (0.65-0.88 V) which shift cathodically from 2 to 5.…”
Section: Solution Electrochemistrymentioning
confidence: 99%
“…We attribute the negligible influence of these ligands on the photophysical properties of the compounds to the fact that the aryl rings are significantly rotated out of co-planarity with the metallacycle (see Table 2) and, thus, conjugation between the rhodium atom and the substituent on the acetylide ligands is not increased. For this reason, rhodacyclopentadiene 3 c with ÀCCÀCCÀ(p-C 6 H 4 À NPh 2 ) [24] as a ligand was synthesized, in which the two alkynyl groups were initially anticipated to ensure co-planarity of the aryl rings. However, despite the additional alkyne unit, the absorption and emission spectra of 3 c are similar to 3 a/b and 3 d. A molecular modeling study showed that steric hindrance between the p-phenylene ortho-hydrogen atoms of the ÀC CÀCCÀ(p-C 6 H 4 ÀNPh 2 ) ligand and the adjacent aryl ring on the diethynylmetallacycle again prevents the desired co-planarity.…”
Section: Photophysical Studiesmentioning
confidence: 99%
“…9 Nevertheless, this structural flexibility does not detract from the impressive electronic properties of oligoynes, which offer considerable interest for their electronic, opto-electronic and electrical charge transport properties. 10 Despite their apparent chemical simplicity it is a challenge to synthesize long carbon chains due to potential instability of R-(C≡C) x -H intermediates and also instability of the longer oligoyne products for certain, particularly small, R groups. This issue was circumvented by Bohlmann who introduced bulky tertiary butyl ( t Bu) end groups in an n = 7 oligomer ( t Bu-(C≡C) 7 -t Bu), 11 and then also by Johnson and Walton, who extended the chain to t Bu-(C≡C) 12 -t Bu.…”
Section: Introductionmentioning
confidence: 99%